High Pressure Structure of Carbonic Acid - Dr John Loveday; Mr Bernhard Massani; Dr Andreas Hermann; Dr Craig Bull (ISIS Facility, 2018)
Recent published studies have identified a stable solid form of carbonic acid at high pressure. This proposal is for beamtime to collect the data to solve its crystal structure.